El tratamiento contable de los ingresos de actividades ordinarias y los costos relacionados con los contratos de construcción - Tinoco Peñaloza, Mónica Elizabeth (2015)
Chapter I of this work is developed titling diagnosis under study which comprises the concepts, rules or diagnostic approaches, which I write scientific articles analyzing and international accounting standards.The description of the diagnostic process performed using the research techniques such as interviews and observation,The analysis of the context and development of the matrix of requirements based on the needs and requirements found in the entity, Justification in terms of work is justified because it is a document produced for obtaining my university degree. Chapter II is structured by the development of integrative proposal as effected, the description of the proposal and methods employ, to implement it, The overall objective which is based on the application of IAS 11 and 18 for the correct accounting for construction contracts, and to determine the veracity and results of operations obtained, The specific objectives which are; Make a diagnosis of the accounting process of the company A & G Construction, to establish what form of accounting for construction contracts, analyze the incidents that have construction contracts in determining the results, diagnose the factors that affect the determination of revenues from construction structural components that is the proposal, the phases of implementation and logistical resources needed for the proposal. Chapter III was drafted on the assessment of the technical, economic, social and environmental feasibility of the proposal and finally the conclusions and recommendations which the author suggests the entity to implement the project